A thermally insulating vermiculite nanosheet–epoxy nanocomposite paint as a fire-resistant wood coating. Issue 14 (22nd June 2021) - Sethurajaperumal, Abimannan; Manohar, Anagha; Banerjee, Arghya; Varrla, Eswaraiah; Wang, Hao; Ostrikov, Kostya (Ken)
Abstract : A nanocomposite made of exfoliated vermiculite nanosheets and epoxy is developed for extinguishing fire and protecting wood from fire degradation. Abstract : Conventional fire-retardant composite coatings are typically made of organic-based materials that reduce flame spread rates. However, the associated chemical reactions and starting precursors produce toxic and hazardous gases, affecting the environment and contributing to climate change. Wood is one of the most common materials used in construction and households, and thin-film fire-retardant coatings are needed to protect it from fire. Here, we derive high-performance nanocomposite paint-based coatings from naturally occurring and highly insulating layered vermiculite. The coatings are made using different weight percentages of shear-exfoliated vermiculite nanosheets in an epoxy matrix and are brush-coated onto teak wood. A series of tests using coated wooden rods and standard fire retardancy tests confirm a reduction in flame spread and combustion velocity with minimal toxic smoke release. Samples coated with the vermiculite/epoxy nanocomposite paint resist fire propagation, and post-combustion analysis indicates their resistance to thermal degradation. Our results offer a novel and eco-efficient solution to minimize the flame propagation rate, enhancing char development, and expand the scope of applications of ultra-thin vermiculite in nanocomposite coatings as a fire retardant, exploiting its low thermal conductivity in thermal insulation systems.